1992
DOI: 10.1056/nejm199206113262403
|View full text |Cite
|
Sign up to set email alerts
|

Combined Chemotherapy and Radiotherapy Compared with Radiotherapy Alone in Patients with Cancer of the Esophagus

Abstract: Concurrent therapy with cisplatin and fluorouracil and radiation is superior to radiation therapy alone in patients with localized carcinoma of the esophagus, as measured by control of local tumors, distant metastases, and survival, but at the cost of increased side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

34
1,069
12
43

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,880 publications
(1,158 citation statements)
references
References 18 publications
34
1,069
12
43
Order By: Relevance
“…The value of chemoradiotherapy for the treatment of unresectable oesophageal carcinoma remains controversial, and only a few clinical studies have been published since the 1980s (Leichman et al, 1984;Leichman et al, 1987;Poplin et al, 1987;Coia et al, 1991;Herskovic et al, 1992;Frorastiere et al, 1993;Poplin et al, 1994). Most patients in these studies had local -regional disease (UICC stage I or II).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of chemoradiotherapy for the treatment of unresectable oesophageal carcinoma remains controversial, and only a few clinical studies have been published since the 1980s (Leichman et al, 1984;Leichman et al, 1987;Poplin et al, 1987;Coia et al, 1991;Herskovic et al, 1992;Frorastiere et al, 1993;Poplin et al, 1994). Most patients in these studies had local -regional disease (UICC stage I or II).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of a continuous irradiation course combined with 5-FU and CDDP indicated that grade 3 and higher leukocytopenia and oesophagitis occurred in 33 -54% and 48 -50% of patients, respectively (Herskovic et al, 1992;Poplin et al, 1994). It is likely that severe leukocytopenia and oesophagitis frequently occurred in a continuous irradiation course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodality treatment plays an increasingly important role in the treatment of oesophageal cancer. Chemotherapy with concurrent radiotherapy has been shown to be superior to radiotherapy alone in patients with locoregional disease (Herskovic et al, 1992). However, pre-operative treatment with chemotherapy remains still investigational because a number of randomised studies have provided conflicting results (Kok et al, 1997;Kelsen et al, 1998;Clark, 2000).…”
mentioning
confidence: 99%
“…There is some evidence to support the addition of chemotherapy to radiotherapy in locally advanced disease; in one study, 2 year survival rate was increased from 10% to 38% (Herskovic et al, 1992 …”
mentioning
confidence: 99%